2013
DOI: 10.1161/hypertensionaha.111.00214
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Obesity, Change in Weight Status, and Hypertension

Abstract: We sought to determine whether change in weight status between adolescence and young adulthood was associated with the risk of developing hypertension among adolescents and whether gender and racial/ethnic group differences existed in the National Longitudinal Study of Adolescent Health. The sample was restricted to participants who self-identified as African-American, Hispanic or White Non-Hispanic (N=8543). Height and weight were measured in adolescence (mean 16yrs), and again in adulthood (mean 29yrs). We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 16 publications
2
27
1
4
Order By: Relevance
“…Thomas et al (46) further hypothesized that increased sympathetic nervous system stimulation in the black population might be an underlying cause for development of hypertension. Similarly, an increased prevalence of hypertension was observed in the Hispanic population (3,10,39,44).…”
Section: Original Articlementioning
confidence: 72%
“…Thomas et al (46) further hypothesized that increased sympathetic nervous system stimulation in the black population might be an underlying cause for development of hypertension. Similarly, an increased prevalence of hypertension was observed in the Hispanic population (3,10,39,44).…”
Section: Original Articlementioning
confidence: 72%
“…Even obese children and adolescents who lost weight by shifting to overweight or healthy weight had modest increases in SBP percentile; these patterns are consistent with others in the literature. 12,23 Of particular interest, a small percentage of obese and severely obese children and adolescents had a reduction in BMI to the healthy weight category. Because this study relied on a retrospective EHR review, we do not have data that might explain this change, other than there were no significant differences in the annual visit rate among the weight change categories.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Previous studies have reported significant associated changes in BMI and BP from childhood to early adolescence 10,11 and in BMI and BP from adolescence to mean age 29 years. 12 Other studies have demonstrated a strong association between change in BMI z score and change in BP in adolescents. [13][14][15] In a recent metaanalysis of cross-sectional studies of BMI and cardiovascular disease risk factors in otherwise healthy children, overweight and obese children had systolic BPs 4.5 and 7.5 mm Hg higher compared with healthy weight children.…”
mentioning
confidence: 94%
“…34,36,37 Childhood adversity has been associated with obesity in children as young as 5 years of age, 45 and prospective research shows that childhood obesity and adolescent obesity have been associated with increased risk of cardiovascular risk factors and CVD among adults. [53][54][55] Data also suggest that whereas an unhealthy diet and sedentary lifestyle adversely affect physical and mental health, 56,57 a healthy diet and plentiful activity reduce inflammation, depression, and anxiety. 58,59 Thus, evidence increasingly suggests that behavioral risk factors, in part, mediate the childhood adversity-cardiometabolic disease relationship.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%